2018
DOI: 10.3390/app8060999
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Bowel Motility Evaluation Technique for Noncontact Sound Recordings

Abstract: Information on bowel motility can be obtained via magnetic resonance imaging (MRI)s and X-ray imaging. However, these approaches require expensive medical instruments and are unsuitable for frequent monitoring. Bowel sounds (BS) can be conveniently obtained using electronic stethoscopes and have recently been employed for the evaluation of bowel motility. More recently, our group proposed a novel method to evaluate bowel motility on the basis of BS acquired using a noncontact microphone. However, the method re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The team achieved automated BS identification through an autoregressive moving average of 91% accuracy and concluded that BS duration reflects intestinal motility [ 73 ]. The group successfully applied unsupervised BS detection in non-contact recordings and determined three clinically pertinent parameters: sound-to-sound interval, which was associated with frequency (per minute), as well as the ratio of signal to noise [ 74 ]. These achievements can be considered a successful application of artificial intelligence-based BS detection in non-contact recordings.…”
Section: Resultsmentioning
confidence: 99%
“…The team achieved automated BS identification through an autoregressive moving average of 91% accuracy and concluded that BS duration reflects intestinal motility [ 73 ]. The group successfully applied unsupervised BS detection in non-contact recordings and determined three clinically pertinent parameters: sound-to-sound interval, which was associated with frequency (per minute), as well as the ratio of signal to noise [ 74 ]. These achievements can be considered a successful application of artificial intelligence-based BS detection in non-contact recordings.…”
Section: Resultsmentioning
confidence: 99%
“…Microphone-based sensors are popular for BS recording [14,15,16,17,18,19,20]. In 2013, Sakata et al developed a silicon microphone-based sensor for long-term BS recording [15].…”
Section: Introductionmentioning
confidence: 99%
“…Since microphone-based sensors are sensitive to airborne noise, the ambient noise might easily contaminate the BS signal. Emoto et al proposed a non-contact microphone for BS recorded and used their system to identify gut motility before and after soda intake [19,20]. However, their participants were required to lie down on a bed for recordings, which is inconvenient for long recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Rekanos and Hadjileontiadis proposed an iterative kurtosis-based technique for the detection of bowel sound in 2006 [11], and Ulusar developed a gastrointestinal motility monitoring system using a Naive Bayesian algorithm for BS observation in 2014 [12]. Subsequently, several advanced machine learning techniques were employed for BS detection, including support vector machine (SVM) [13], artificial neural network (ANN) [14,15], and long short term memory (LSTM) [16] approaches, and have achieved better results than the traditional methods. However, even these advanced models have some limitations.…”
mentioning
confidence: 99%